Pto Interaction Proteins: Critical Regulators in Plant Development and Stress Response - Sun, Meihong; Qiu, Liuliu; Liu, Yanshuang; Zhang, Heng; Zhang, Yongxue; Qin, Yi; Mao, Yingjie; Zhou, Min; Du, Xiaosha; Qin, Zhi; Dai, Shaojun (Frontiers in Plant Science, 2022)
Pto interaction (Pti) proteins are a group of proteins that can be phosphorylated by serine/threonine protein kinase Pto, which have diverse functions in plant development and stress response. In this study, we analyzed the phylogenetic relationship, gene structure, and conserved motifs of Pti1s and predicted the potential cis-elements in the promoters of Pti1 genes using bioinformatics methods. Importantly, we systematically summarized the diverse functions of Pti1s in tomato, rice, Arabidopsis, potato, apple, and cucumber. The potential cis-elements in promoters of Pti1s decide their functional diversity in response to various biotic and abiotic stresses. The protein kinase Pti1 was phosphorylated by Pto and then modulated the downstream signaling pathways for PTI and ETI in the disease insistence process. In addition, some transcription factors have been defined as Ptis (e.g., Pti4, Pti5, and Pti6) originally, which actually were ethylene-response factors (ERFs). Pti4, Pti5, and Pti6 were modulated by salicylic acid (SA), jasmonate (JA), and ethylene signaling pathways and regulated diverse defense-related gene expression to cope with Pst infection and insect wounding.